The Consequences of Radical Patent-Regime Change - Alexander Donges; Felix Selgert (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper analyzes the consequences of radical patent-regime change by exploiting a natural experiment: the forced adoption of the Prussian patent system in territories annexed after the Austro-Prussian War of 1866. Compared to other German states, Prussia granted patents more restrictively by setting higher novelty requirements. Though, patent fees were much lower. By using novel hand-collected data, we show that the forced adoption of the Prussian patent law caused a massive drop in the number of patents per capita in annexed territories. By contrast, we find a significantly positive effect of patent-regime change on world-fair exhibits per capita, which we use as a proxy for non-patented innovation. We interpret this finding as evidence that restricting the granting of patents, which creates more competition, is conducive for the generation of innovation.
Keywords: D2; K11; L51; N0; O14; 330; Innovation; Intellectual Property; Patents; Patent Law; Technological Change